1967
DOI: 10.1002/j.1537-2197.1967.tb10737.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genome and Species Relationships in the Polyploid Wheats by Protein Electrophoresis

Abstract: Protein spectra from 4n and 6n species of Triticum were obtained by electrophoresis of seed extracts on polyacrylamide gels. Homologies among the species with regard to protein bands were tested by comparing each species with the standard T. dicoccum in a protein mixture spectrum. By reference to two pairs of homologous bands, each spectrum was then adjusted to the migration velocity of the standard by photographic enlargement. The homologies were found to be consistent with evidence from conventional methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
2

Year Published

1969
1969
1975
1975

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 18 publications
1
28
0
2
Order By: Relevance
“…On a examin6 par 6lectrophorbse sur gel de (Johnson et al 1967;Barber et al 1968;Boyd et al 1969;Jaaska 1972;Johnson 1972). Elton and Ewart (1962) and Graham (1963) Chen and Bushuk (1970).…”
unclassified
“…On a examin6 par 6lectrophorbse sur gel de (Johnson et al 1967;Barber et al 1968;Boyd et al 1969;Jaaska 1972;Johnson 1972). Elton and Ewart (1962) and Graham (1963) Chen and Bushuk (1970).…”
unclassified
“…Less resolution is provided in the slower gliadin series (21,23), between the origin and -4.0 cm; therefore, conclusions regarding band homologies are based largely on the faster moving albumin series comprising the rest of the pattern. The accessions included in Figs.…”
mentioning
confidence: 99%
“…Johnson et al (1967) and Johnson (1967) showed that the electrophoretic patterns of seed proteins of Emmer and Timopheevi groups were clearly distinguishable from each other, after examining eight Emmer-and four Timopheevi-group taxa. However, as mentioned above, Waines (1970) found two electrophoretically different types in a species of Timopheevi group, T. araraticurn, one of which was identical to T. timopheevi but the other to T. dicoccum, a species belonging to Emmer group.…”
Section: Discussionmentioning
confidence: 96%
“…nudiglumis collected in northern Iraq (studied by Sachs 1953and Wagenaar 1961) and a T. dicoccoides accession from eastern Turkey (studied by Wagenaar 1966), both of which are very similar to T. timopheevi cytologically thus generally regarded as the members of Timopheevi group (Wagenaar 1966;Feldman 1966;Johnson et al 1967). Rao and Smith (1968) and Dagan and Zohary (1970) later found some cytologically Emmer-group tetraploids (Israeli race by Harlan and Zohary 1966) of wild type among the collections from Turkey and western Iran, respectively.…”
Section: Discussionmentioning
confidence: 99%